Phthalate and DINCH urinary concentrations across pregnancy and risk of preterm birth. (1st January 2022) - Yland, Jennifer J.; Zhang, Yu; Williams, Paige L.; Mustieles, Vicente; Vagios, Stylianos; Souter, Irene; Calafat, Antonia M.; Hauser, Russ; Messerlian, Carmen; ,
Abstract: Preconception and prenatal exposure to phthalates has been associated with an increased risk of preterm birth. However, it is unclear whether there are periods of heightened susceptibility during pregnancy. This prospective cohort study included 386 women undergoing fertility treatment who gave birth to a singleton infant during 2005 through 2018. Eleven phthalate metabolites were measured in spot urine samples collected at each trimester. In approximately 50% of participants, two metabolites of 1, 2-cyclohexane dicarboxylic acid diisononyl ester (DINCH), a phthalate substitute, were also measured. The molar sum of four di(2-ethylhexyl) phthalate metabolites (∑DEHP) was calculated. We evaluated the associations of mean maternal biomarker concentrations with risk of preterm birth using modified log-binomial models and utilized multiple informant models to compare trimester-specific associations. We examined the relative biomarker concentration across gestation comparing women with preterm birth to women with term delivery using quadratic mixed model. The risk ratio for preterm birth associated with a one-unit increase in the natural log-transformed urinary concentrations of ∑DEHP (mean during pregnancy) was 1.21 (95% confidence interval (CI): 0.84, 1.72). In multiple informant models, these associations were strongest in the third trimester (RR = 1.51; 95% CI: 1.17, 1.95). Estimated mean ∑DEHP concentrations were higher among women with preterm than term delivery, especially late in gestation. Associations with preterm birth were also observed for each of the four individual DEHP metabolites. Detection of cyclohexane-1, 2-dicarboxylic acid monocarboxyisooctyl ester (MCOCH), a metabolite of DINCH, appeared to be positively related to preterm birth. In this prospective cohort of subfertile couples, maternal ∑DEHP metabolite concentrations during pregnancy were associated with an increased risk of preterm birth, particularly during late gestation. Graphical abstract: Image 1 Highlights: Prenatal phthalates and phthalate substitutes were investigated in relation to preterm birth. Mean prenatal DEHP concentration was associated with preterm birth, though results were imprecise. Associations were strongest with third trimester DEHP exposure, suggesting a vulnerable window. MCOCH, a phthalate substitute metabolite, may also be associated with preterm birth.